A prospective open label study of efficacy and tolerability of topical tacrolimus in Vitiligo - Bai, A. Suguna; Sujatha, G.; Preetha, N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Vitiligo is a cosmetically and psychologically devastating clinical conundrum with various hypotheses of etiology inclusive of an immunological one too. Long term clinical visits, various adverse effects and cost of therapy are the major limitations of current treatment of vitiligo. Topical Tacrolimus which has been tried and found useful in various skin conditions with immunological basis was evaluated for its efficacy and tolerability compared with the available standard treatment of Topical Betamethasone. Methods: The study was done in the outpatient unit of Department of Dermatology, Stanley medical college, for duration of six months. Newly diagnosed vitiligo patients attending the outpatient clinic were taken for the study. A randomised, open labelled, comparative study of efficacy and tolerability of Topical Tacrolimus in vitiligo was done. Results: Early onset of repigmentation, higher mean repigmentation with no significant side effects systemically or topically were observed in the study group compared to the control group. Conclusions: This study shows that Topical Tacrolimus produces rapid and significant repigmentation with less significant side effects in vitiligo. Topical Tacrolimus is more efficacious and better tolerated than available standard Topical Betamethasone.